Improving the quality of discharge summaries: implementing updated Academy of Medical Royal Colleges standards at a district general hospital - May-Miller, Hannah (BMJ Qual Improv Rep, 2015)
Quality of documentation is harder to quantify and incentivise, but it has a significant impact on patient care. Good discharge summaries facilitate continuity between secondary and primary care. The junior doctors’ forum led this project to improve the quality of electronic discharge summaries (eDS). Baseline measurement revealed significant room for improvement. We measured the quality of 10 summaries per month (across all inpatient specialties), against 23 indicators from the revised Academy of Medical Royal Colleges (AoMRC) standards (2013) that were prioritised by GPs as a “minimum dataset”. Junior doctors felt that the Trust's dual eDS systems were responsible for great variation in quality. This was confirmed by the results of a comparison audit of the systems in April 2014: one system greatly outperformed the other (57% mean compliance with iSoft clinical management (iCM) based system vs. 77% with InfoPath-based system). We recommended that the Trust move to a single eDS system, decommissioning the iCM-based system, and this proposal was approved by several Trust committees. We worked with information services, junior doctors, general practitioners and hospital physicians to develop and implement a generic template to further improve compliance with AoMRC standards. In August 2014, the iCM-based system was withdrawn, the new template went live, and training was delivered, coinciding with the changeover of junior doctors to minimise disruption. Median compliance increased from 66.7% to 77.8%. Quality of discharge summaries had improved across the specialties. There was a reduction in the number of complaints and positive qualitative feedback from general practitioners and junior doctors. Completion of discharge summaries within 24 hours was not affected by this change. There is still more to be done to improve quality; average compliance with the full AoMRC standards (39 indicators) is 59.5%. With the approval of the Trust executive committee further plan, do, study, act (PDSA) cycles are underway, working to improve the remaining specialty-specific templates.